Hegel’s Concept of State - Mansoor Akbar Kundi & Safia Bano (Journal of Political Studies, 2020)
Western Political philosophers have spoken about the concept of state and society in large. From Plato to Noam Chomsky one can read thinkers’ approach about state, its structure and Implications. Each interpreted the concept of state according to the time he lived in and surroundings of state and societal institutions. With all differences and similarities the thinkers agreed and disagreed with one another. Hegel is one of the famous political thinkers who living in the agof of transition and change in the wake of French Revolution. To him, state is an institution of highest social, political and ethical culmination and exists for promotion of human freedom.